A National Examination of Caregiver Use of and Preferences for Support Services: Does Rurality Matter?. (October 2019) - Henning-Smith, Carrie; Lahr, Megan; Casey, Michelle
Objective: The objective of this study was to assess rural–urban differences in caregiver use of and preferences for support services.Method: Using the 2015 Caregiving in the U.S. survey data ( n = 1, 389), we analyzed rural–urban differences by caregiver residence in use of and preferences for support services. We analyzed bivariate differences in service use and preferences, as well as in sociodemographic and caregiving relationship characteristics. We also assessed the correlates of service use using stratified ordered logistic regression models.Results: Approximately one third of all caregivers had used no supportive services, with few differences in service use and preference by location. For caregivers in both locations, having more financial strain was associated with greater use of services.Discussion: This article identifies broad needs for caregiver support across all geographic locations. Targeted efforts should be made to ensure access to supportive services accounting for unique barriers by geography.